2022
DOI: 10.3389/fphar.2022.848251
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanism of 5-HT/NE/DA Triple Reuptake Inhibitor on Adult Depression Susceptibility in Early Stress Mice

Abstract: Major depressive disorder (MDD) is a chronic, remitting and debilitating disease and the etiology of MDD is highly complicated that involves genetic and environmental interactions. Despite many pharmacotherapeutic options, many patients remain poorly treated and the development of effective treatments remains a high priority in the field. LPM570065 is a potent 5-hydroxytryptamine (5-HT), norepinephrine (NE) and dopamine (DA) triple reuptake inhibitor and both preclinical and clinical results demonstrate signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Besides GABA and Glu indicated above, 5-HT, a monoamine neurotransmitter regulates emotions and cognitive functions in the CNS [35]. NE, DA, etc., are important indicators for assessing depression severity [36]. Also, research has demonstrated a strong correlation between dopamine, 5-HT, norepinephrine, and serotonin in the brain with depression-like emotions [37], which is in agreement with our findings [38].…”
Section: Discussionsupporting
confidence: 92%
“…Besides GABA and Glu indicated above, 5-HT, a monoamine neurotransmitter regulates emotions and cognitive functions in the CNS [35]. NE, DA, etc., are important indicators for assessing depression severity [36]. Also, research has demonstrated a strong correlation between dopamine, 5-HT, norepinephrine, and serotonin in the brain with depression-like emotions [37], which is in agreement with our findings [38].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, DA is converted into noradrenaline (NA) by DA hydroxylase. Numerous studies ( 72 83 ) confirmed that the dysfunction of monoamine neurotransmitters such as NE, DA, and 5-HT plays a crucial part in the pathogenesis of depressive disorder. Elevated DA, L-DOPA, and vanillylmandelic acid (VMA) levels were found in the hippocampus of CSDS-induced model mice ( 84 , 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Products were purified by silica gel column chromatography (200−300 mesh, Qingdao, China). 1 H NMR spectra and 13 C NMR spectra were recorded on Bruker AVANCE instrument at 25 °C using TMS as the internal standard in CDCl 3 or DMSO-d 6 . ESI-MS spectra were recorded on a HP 1100LC/MSD spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Depression is a major public health problem, ranking the third leading cause of the global burden of disease and WHO predicts that the disorder will rank first by 2030. 1 Despite many progresses in the development of antidepressants, the clinical use of currently available treatments for depression are limited, as they are not always effective and cause various adverse effects. 2 Thereby, searching for new therapeutic alternatives to treat this mental disorder more effectively and work faster and safer is an urgent need.…”
Section: Introductionmentioning
confidence: 99%